The Gyan Burman Fellowship in gastrointestinal surgery at Sir Ganga Ram Hospital: A global perspective based on feedback from former fellows - Sameer Mukundkumar Pandya; Samiran Nundy; Parmanand Tiwari (Current Medicine Research and Practice, 2024)
Background: The 3-month Gyan Burman Fellowship (GBF) in Surgical Gastroenterology and Liver Transplantation at Sir Ganga Ram Hospital in New Delhi has been offered to aspiring surgeons worldwide since 2003. Using a questionnaire, we evaluated whether the experience had been useful to its past candidates. Aims: Our aim was to evaluate how useful the experience had been to its past candidates. Materials and Methods: We sent a standard questionnaire online to 100 of the 138 fellows whom we were able to contact and who had graduated up to 31st December 2022. The data were collected on pre-designed data sheets, entered in a computer and analysed. Results: We received 69 responses. Sixty-one (88.4%) were male, and 8 (11.6%) were female. They came from 15 different developing countries. The GBF was the primary choice for training for 59 (85.5%), and 40 (58%) came because they did not have any equivalent training available locally. They said that overall the 3-month fellowship had had a positive impact on both the careers of the trainees and their respective regions' healthcare. The experience was reported to have been excellent by 40 (60%). Conclusion: The 3-month GBF has been useful to most of its candidates and has provided them with knowledge on the quality of their surgical care in their local healthcare centres.